IMPLEMENTASI KEBIJAKAN PUBLIK PADA SISTEM ZONASI DALAM PENERIMAAN PESERTA DIDIK BARU (PPDB) DI UPTD SMP NEGERI 2 BALONGAN KABUPATEN INDRAMAYU - Ian Ardianto (Demagogi: Journal of Social Sciences, Economics and Education, 2025)
The implementation of the new student admission zoning system (PPDB) is part of a broader initiative aimed at promoting educational equality in Indonesia. The zoning system has shown promise in promoting educational equality, but there are still challenges that require ongoing evaluation and adjustment to ensure its effectiveness in the long term. This study aims to analyze the new student admission process with an emphasis on the implementation of the zoning policy. Through the method of interviews with related parties, the study conducted seeks to further investigate how effective the policy is, the obstacles and problems faced, and analyze its impact on improving the quality of education and public services provided by educational institutions. In this article, the theory used is about Public Policy. according to George C. Edward III's Theory in 1980. The method in this article is a qualitative method by conducting in-depth interviews. The results obtained The implementation of the PPDB system ran smoothly and according to the rules, supported by good resources, communication, bureaucracy, and commitment. Although effective in equalizing access and quality of education, this system faces obstacles such as limited school capacity, manipulation of domicile data due to disparities between schools, and challenges in parents' digital literacy. Improving infrastructure, socialization, and reducing disparities between schools are crucial for optimal success.